THE THEORETICAL BASICS OF THE POST-SOVIET MEDIA - Shoshitashvili, Nino (European Scientific Journal, ESJ, 2016)
Media plays a huge role in a political life of society; it has an impact on a political agenda of society, it has significantly contributed to building of the pluralistic society and a state. Today, on the agenda of ongoing reforms in Georgia are governance ensurance that is based on the democratic principle, and this is why mass media means represent one of most important social institutions, which should support the state development in this direction.Media, as an important instrument of political processes, gains especially great importance when it merges with political sphere.It’s important, that in modern politology mass communication means are charactarized by such a superior "titles" like "The great arbitrator", "fourth power", etc. Belief in the omnipotence of television is so great that the political figures believe - who controls the media controls the whole country. And indeed, the modern politics is impossible without the mass media. Media creates monitoring of political processes, confrontation of the political positions and ensuring their public relations space. It is natural that it takes an important part in the development of the Georgian statehood, especially in The Post-Soviet period. Because of such a significant role of the media in public and political life, the research of the mass information means is a subject of the constant discussion and consideration among scientists, as well as experts and journalists themselves.